Adhesion and segregation characteristics of crumb rubberized binders based on solution-soaked methods. (20th June 2022) - Badughaish, Abdulrahman; Li, Jin; Amirkhanian, Serji; Xiao, Feipeng
Abstract: The increasing waste tires have posed a great challenge to the environment. Meanwhile, the potential advantages of using waste tire crumb rubber (CR) as the modifier of paving asphalt materials have attracted the attention of many researchers. However, the weak compatibility between the asphalt matrix and CR called researchers to make further attempts. In this study, the soaking pretreatments of CR in various solutions were used to boost the interfacial compatibility of CR to the asphalt and further improve the performance of rubberized asphalt, by chemically activating the CR surface. It was found that the three peaks appeared at a wavenumber of 2914 cm −1, 2847 cm −1, and 1429 cm −1 after solution soaking pretreatments, which represented the CH2 played an important role in the process. Besides, the lowers the area of these peaks, the greater the CR-asphalt compatibility. Furthermore, soaking the CR in the heated water slightly decreased the adhesion strength of rubberized asphalt and increased the segregation degree between the CR and asphalt. On the other hand, soaking the CR in potassium permanganate and the mixed solutions of sodium hydroxide and potassium permanganate significantly increased the adhesion strength of rubberized asphalt and decreased the segregation degree between the CR and asphalt.